2022
DOI: 10.1039/d2nr04239h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall zirconium carbide nanodots for synergistic photothermal-radiotherapy of glioma

Abstract: Glioma is characterized by highly invasive, progressive, and lethal features. In addition, conventional treatments have been poorly effective in treating glioma. To overcome this challenge, synergistic therapies combining radiotherapy (RT)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Liquid-phase exfoliation is usually conducted by sonifying the material in an appropriate solvent and is a simple top-down approach to the production of numerous nanomaterials. Additionally, this liquid-phase exfoliation is an efficient method for synthesizing different types of metal compound nanomaterials, including TiH 1.924 and TiN. , The synthesis process of TiO NSs was primarily realized by liquid-phase ultrasonic exfoliation technology (Figure a). TEM images demonstrated that the TiO NSs were irregularly dispersed nanosheet structures, with an average diameter of approximately 50 nm (Figure b–e).…”
Section: Resultsmentioning
confidence: 99%
“…Liquid-phase exfoliation is usually conducted by sonifying the material in an appropriate solvent and is a simple top-down approach to the production of numerous nanomaterials. Additionally, this liquid-phase exfoliation is an efficient method for synthesizing different types of metal compound nanomaterials, including TiH 1.924 and TiN. , The synthesis process of TiO NSs was primarily realized by liquid-phase ultrasonic exfoliation technology (Figure a). TEM images demonstrated that the TiO NSs were irregularly dispersed nanosheet structures, with an average diameter of approximately 50 nm (Figure b–e).…”
Section: Resultsmentioning
confidence: 99%
“…To resolve the excess ROS problems caused by PPT, Xianwen Wang and his colleagues designed ultrasmall ZrC NDs, which eliminates ROS to decrease inflammation caused by PTT treatment for glioma ( 92 ). Subsequently, ultrasmall ZrC–PVP nanodots (NDs) (ZrC–PVP NDs) based on the combination of PTT–RT photothermal therapy (PTT) -Radiation therapy (RT) was designed for glioma treatment ( 93 ). Furthermore, they attempted to disrupt the respiration process and modify the oxidation state of cancer cells by continuously generating H 2 through the transfer of MgG rods into the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there exists hypoxia in most solid tumors while oxygen is essential to enhance radiation-induced DNA damage, hence the tumor hypoxia-associated radiation resistance is another mechanism that limits the radiotherapy effectiveness ( 56 58 ). In conjunction with the advancement in nanotechnology, nanomedicine strategies will hopefully be used to enhance tumor radiation responses and overcome radio resistance ( 59 62 ).…”
Section: Nanotechnology-based Therapeutics For Lung Cancermentioning
confidence: 99%